The Influence of the Environment on Understanding the Arabic Language Lesson for Eighth Grade Students at Secondary School | تأثير البيئة لفهم الدرس اللغة العربية لطلبة الفصل الثامن في المدرسة الثانوية - Wahab, Abdul; Syaifullah, Muhammad; Roza, Ahmad Subhan (An-nahdloh : Journal of Arabic Teaching, 2024)
The environment has a big influence on students' understanding of Arabic language lessons. This research aims to determine the influence of the environment, especially the family, school and community environment, on the understanding of Arabic language lessons for class VIII students at MTs Darun Najah Sambikarto. This research uses a quantitative approach with a quasi-experimental method. Data collection techniques are carried out through observation, interviews, tests and documentation. Data were analyzed using validity, reliability, normality, homogeneity and hypothesis testing. From the posttest results, a significant value was obtained of 0.007 <0.05. Where the significant value obtained is <0.05, the hypothesis that reads is "The environment influences the understanding of Arabic language lessons for class VIII students at MTs Darun Najah Sambikarto for the 2023-2024 academic year. A conducive environment such as a supportive family, positive peers, and learning activities at Islamic boarding schools can improve students' understanding of Arabic language lessons. This research provides recommendations on the importance of creating a good environment so that students can understand Arabic lessons more easily. It is hoped that future researchers will be able to provide new explanations about the importance of the environment in understanding Arabic language lessons, especially in the field of education. So this theory will persist and it is hoped that it will become more widespread.